2004
DOI: 10.1111/j.1399-3038.2004.00125.x
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status and prevalence of allergic rhinitis and atopic eczema symptoms in young adolescents

Abstract: Environmental factors are known to influence the development of allergic rhinitis and atopic eczema in genetically susceptible individuals. Socioeconomic status (SES) may be an important indicator of risk for these conditions. The International Study of Asthma and Allergies in Childhood (ISAAC) Phase 1 written questionnaire was used to determine the prevalence and severity of allergic rhinoconjunctivitis and atopic eczema symptoms in 4947 pupils aged 13-14 years attending 30 schools in socioeconomically divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
66
2
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 36 publications
8
66
2
1
Order By: Relevance
“…In common with other studies undertaken in South Africa 14 and in Brazil, 15 we found that the prevalence of allergic rhinitis was higher among patients living under better socioeconomic conditions. Our data are in agreement with data obtained in epidemiological studies of asthma, such as that carried out by Britto et al in Recife, reporting a higher prevalence of asthma in private schools and among children whose parents had spent longer in education.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…In common with other studies undertaken in South Africa 14 and in Brazil, 15 we found that the prevalence of allergic rhinitis was higher among patients living under better socioeconomic conditions. Our data are in agreement with data obtained in epidemiological studies of asthma, such as that carried out by Britto et al in Recife, reporting a higher prevalence of asthma in private schools and among children whose parents had spent longer in education.…”
Section: Resultssupporting
confidence: 70%
“…The first study carried out in Latin America using this protocol, (phase I) took place in São Paulo, and after that six research projects were run in other Brazilian cities, investigating a total of 20,587 adolescents aged [13][14] years. According to the authors, the mean prevalence of diagnosed rhinitis was 34.2%, and the mean prevalence of allergic rhinitis was 18%.…”
Section: Resultsmentioning
confidence: 99%
“…The questionnaire was also made available in English and Afrikaans, which are the other two languages spoken in the area. The Afrikaans version was already available from the first Cape Town ISAAC study [13].…”
Section: Sampling and Proceduresmentioning
confidence: 99%
“…This is the fifth study that applied the ISAAC methodology in the SADC region. ISAAC Phase I and III studies were conducted in South Africa during 1995 and 2002 in the urban setting of Cape Town [13,14]. ISAAC Phase III studies were also conducted in urban, suburban and semi-rural areas in Maputo, Mozambique during May 2004 and in Kinshasa, the Democratic Republic of Congo [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…So other factors should be considered for the increase in the prevalence of AE. 16,33,34 In our study we did not find any association between the symptoms of AE and the level of socioeconomic status related risk factors including education level of mother and father, annual family income, number of people living in home, sharing bedroom, heating system, bathed in sunlight house. In a study in Spanish schoolchildren, there was no significant association between the type of indoor energy sources (biomass, gas and electricity) used and the presence of AD.…”
mentioning
confidence: 66%